2019
DOI: 10.1017/s0007485319000798
|View full text |Cite
|
Sign up to set email alerts
|

Silicon is an inducible and effective herbivore defence againstHelicoverpa punctigera(Lepidoptera: Noctuidae) in soybean

Abstract: The role of silicon (Si) in alleviating the effects of biotic and abiotic stresses, including defence against insect herbivores, in plants is widely reported. Si defence against insect herbivores is overwhelmingly studied in grasses (especially the cereals), many of which are hyper-accumulators of Si. Despite being neglected, legumes such as soybean (Glycine max) have the capacity to control Si accumulation and benefit from increased Si supply. We tested how Si supplementation via potassium, sodium or calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 48 publications
6
43
0
Order By: Relevance
“…Ferreira, Moraes, and antunes (2011) reported that silicon supplementation in soybean had a detrimental effect on the silverleaf whitefly Bemisia tabaci . Recently, Johnson et al (2017), Johnson, Ryalls, Gherlenda, Frew, and Hartley (2018) showed that silicon supplementation in lucerne slightly benefitted the phloem‐sucking aphid Acyrthosiphon pisum but it was also reported by Johnson et al (2019) that silicon effectively reduced relative growth rate of the Australian native bollworm Helicoverpa punctigera . However, the limited number of studies thus far restricts our understanding of how silicon affects legume–herbivore interactions.…”
Section: Evidence For Silicon Affecting Legumesmentioning
confidence: 94%
See 2 more Smart Citations
“…Ferreira, Moraes, and antunes (2011) reported that silicon supplementation in soybean had a detrimental effect on the silverleaf whitefly Bemisia tabaci . Recently, Johnson et al (2017), Johnson, Ryalls, Gherlenda, Frew, and Hartley (2018) showed that silicon supplementation in lucerne slightly benefitted the phloem‐sucking aphid Acyrthosiphon pisum but it was also reported by Johnson et al (2019) that silicon effectively reduced relative growth rate of the Australian native bollworm Helicoverpa punctigera . However, the limited number of studies thus far restricts our understanding of how silicon affects legume–herbivore interactions.…”
Section: Evidence For Silicon Affecting Legumesmentioning
confidence: 94%
“…weevils) in soil (Johnson et al, 2006). However, silicon supplementation could equally reverse these negative consequences by augmenting plant resistance to herbivores (Frew, Powell, Allsopp, Sallam, & Johnson, 2017; Johnson et al, 2019).…”
Section: Research Questions and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…While researchers continue to debate the biological roles of Si and uncover the mechanisms behind them (Frew et al, 2018;Coskun et al, 2019), we conclude that, at a minimum, Si mitigates the negative impacts of various stressors, such as herbivory, which then enable plants to improve growth potential (Johnson et al, 2019).…”
Section: Effects Of Silicon On Herbivorymentioning
confidence: 71%
“…Several studies have documented effects of soil Si addition on plant chemical defenses (e.g., Reynolds et al, 2009), anti-herbivore phytohormonal signaling (e.g., Hall et al, 2019), and changes in plant nutritional quality (e.g., Frew et al, 2018;Moise et al, 2019). For example, Si may induce indirect defense mechanisms by altering the composition of herbivore-induced plant volatiles that attract herbivore parasitoids and predators (Liu et al, 2017).…”
Section: Effects Of Silicon On Herbivorymentioning
confidence: 99%